P233 Efficacy and safety of once-daily glycopyrronium compared with blinded tiotropium in patients with COPD: the GLOW5 study. (14th November 2013) - Chapman, KR; Beeh, K; Bateman, ED; Beier, J; D'Urzo, AD; Nutbrown, R; Chen, H; Henley, M; Overend, T; D'Andrea, P
Abstract : Background: Glycopyrronium, a once-daily long-acting muscarinic antagonist (LAMA), has demonstrated a similar efficacy and safety profile to open-label tiotropium in patients with moderate-to-severe chronic obstructive pulmonary disease (COPD). 1 The GLOW5 study compared the efficacy and safety of glycopyrronium with blinded tiotropium. Methods: In this multicentre, 12-week, blinded study, patients ≥ 40 years with moderate-to-severe COPD (post-bronchodilator FEV1 ≥ 30% and < 80% of the predicted normal, post-bronchodilator FEV1 /FVC < 0.70) and a smoking history of ≥10 pack-years were randomised to glycopyrronium 50μg (via Breezhaler ® device) or tiotropium 18μg (via HandiHaler ® device). The primary objective was to demonstrate non-inferiority of glycopyrronium versus tiotropium for trough FEV1 at Week 12 (non-inferiority margin: –50 mL). Other endpoints included FEV1 area under the curve from 0 to 4 hours (AUC0–4hr ) on Day 1, Transition Dyspnoea Index (TDI), St George's Respiratory Questionnaire (SGRQ), rescue medication use, exacerbation rate, safety and tolerability. Results: Of the 657 patients randomised, (glycopyrronium [n = 327]; tiotropium [n = 330]; mean age: 63.5 years, mean post-bronchodilator FEV1 : 53.5% predicted), 95.9% completed the study. Glycopyrronium demonstrated non-inferiority to tiotropium for trough FEV1 at Week 12 (Least Squares Mean [LSM] = 1.41L for both the groups; 95% confidence interval [CI]: –0.032, 0.031L). Glycopyrronium had a rapid onset of bronchodilation in the morning as demonstrated by a higher FEV1 AUC0–4hr on Day 1 compared to tiotropium (LSM treatment difference [Td] = 58mL; p < 0.001). At Week 12, TDI total score (Td = –0.188; p = 0.385), SGRQ total score (Td = 0.65; p = 0.488) and percentage of days with no rescue medication use (Td = –1.5; p = 0.528) were comparable between the groups. No significant treatment difference was observed with respect to rate of moderate/severe COPD exacerbations per year (glycopyrronium 0.38 versus tiotropium 0.35 [rate ratio = 1.10, 95% CI: 0.62, 1.93]; p = 0.754). Overall, the incidence of adverse events was similar in the glycopyrronium (40.4%) and tiotropium (40.6%) groups. Conclusion: Glycopyrronium and blinded tiotropium showed similar improvements in lung function, dyspnoea, health status, exacerbation rate and rescue medication use, with a similar safety and tolerability profile. Onset of bronchodilation with glycopyrronium was significantly more rapid following the first dose. Reference: Kerwin, E. et al. Eur Resp J 2012;40:1106–1114.